The safety of intracytoplasmic sperm injection in men with hepatitis B - Zheng, Zhong (Arch Med Sci, 2016)
INTRODUCTION: In this study, we aimed to evaluate the safety of using different sources of sperm when male partners were infected with hepatitis B virus (HBV). MATERIAL AND METHODS: A total of 338 couples receiving their first intracytoplasmic sperm injection (ICSI) cycle at the Department of Reproduction, Ren Ji Hospital, between 2007 and 2012 were enrolled if the female partner tested negative for HBV DNA, HBsAg, HBeAg, HBeAb and HBcAb. Couples were divided into HBV active infection (group B), convalescent infection (group C) and controls (group A). Subgroups were divided by source of sperm: ejaculated sperm and testicular sperm aspiration/percutaneous epididymal sperm aspiration (TESA/PESA) sperm. RESULTS: When using ejaculated sperm for ICSI, two pronuclear (2PN) fertilization rate, implantation rate, clinical pregnant rate, early miscarriage rate and live birth rate showed no significant difference between the three groups. However, in the three TESA/PESA groups, the early miscarriage rate was highest in men with active HBV infection (B2) (23.1%, p = 0.035). The 2PN fertilization rate and CPR were also lower in the active infection group (76.7%, 26.3%) than the convalescent infection (82.9%, 36.2%) and control group (78.2%, 50%), but the difference was not statistically significant. No malformed infant was found in any of these groups. CONCLUSIONS: When men have an active HBV infection, using TESA/PESA sperm may cause lower fertilization, a high miscarriage rate and a lower live birth rate, which indicates that HBV active infection may cause adverse effects on ICSI reproductive performance when using testicular or epididymal aspirated sperm.